Empresa Agroindustrial Pomalca S.A. - Gastañaduy Benel, Alfonso (2003)
Pomalca is one of the oldest sugars producing companies in Peru located on the North coast of the Department of Lambayeque which in the last decades has gone through a long period of crisis. The present study makes an economic and financial evaluation of the possibilities of re-floating and of its convenience as a business opportunity for a private investor.With this purpose it presents a technical diagnosis of the company to the year 2000: it establishes the amounts of losses and obligations it summarizes the process of transfer of actions occurred in the framework of the privatization promoted by the government performs an analysis of the productive indicators and of the accounting parameters and projects a financial plan which estimates the investment and borrowing needs. It concludes that if the proposed plan is executed the project is viable so that "it can be as it was".